2020
DOI: 10.1111/jocn.15380
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between personality traits, caring characteristics and abuse tendency among professional caregivers of older people with dementia in long‐term care facilities

Abstract: Aims and objectives To explore the relationship between personality traits, caring characteristics and abuse tendency among professional caregivers of older people with dementia in long‐term care facilities in China. Background Elder abuse is a serious global health problem and human right violation with high incidence among older people with dementia. There are many investigations about impact factors of risk of abuse among family caregivers of older people with dementia. However, in long‐term care facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…This not only reflected that the dementia caregivers got along well with dementia patients, family members and colleagues, but also reflected from the side that the institutions and dementia caregivers paid great attention to interpersonal communication and service attitude. Comparatively speaking, they paid less attention to the caregiver’s health and most caregivers failed to relieve physical fatigue and psychological weariness in a proper manner in the process of care [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This not only reflected that the dementia caregivers got along well with dementia patients, family members and colleagues, but also reflected from the side that the institutions and dementia caregivers paid great attention to interpersonal communication and service attitude. Comparatively speaking, they paid less attention to the caregiver’s health and most caregivers failed to relieve physical fatigue and psychological weariness in a proper manner in the process of care [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies (Feng et al, 2019; van der Cingel & Brouwer, 2021) have shown that there were still stereotypes about the nursing profession in society, that nursing work was simple and not professional, so that nurses were not respected and recognized as they should be. In addition, this study also found that due to the large workload and difficulty of long‐term care, coupled with their lack of ability, individual nurses were prone to vent their stress in an inappropriate form (Chen et al, 2020), which also exists in other countries (USA, Norway, UK, etc) (Hirt et al, 2022), seriously affects the quality of care and health of seniors. In this regard, nurses in long‐term care facilities should continuously strengthen their professional ethics, increase their humanistic care capabilities, and establish a respectable industry image.…”
Section: Discussionmentioning
confidence: 95%
“…No cenário nacional, uma pesquisa mencionou a depressão na pessoa idosa, como fator de risco para sofrer violência. Em relação aos cuidadores, observou-se elevados níveis de sobrecarga e problemas com álcool como preditores do ato violento (CHEN W, et al, 2019).…”
Section: Discussionunclassified